Selection of drought tolerant wheat genotypes by osmotic stress imposed at germination and early seedling stage (SAARC Journal of Agriculture, 2018)
An experiment on hundred wheat genotypes under different levels of osmotic stress was carried out during 2014 to select the genotype(s) tolerant to drought at germination and early seedling stage. Different levels of osmotic stress were imposed by using polyethylene glycol (PEG). Three osmotic stress levels viz. control (distilled water), 15% PEG solution and 25% PEG solution were used. Among the 100 genotypes the rate of germination percentage, final germination (%), root and shoot dry weight, amount of respiration and vigour index under PEG treatment was found significantly lower than that of control condition. Compared to control condition relative decrease in rate of germination, final germination, amount of respiration and vigour index among the wheat genotypes were found more at 25% PEG than that of 15% PEG treatment. However, the seed metabolic efficiency was significantly higher in wheat genotypes under both 15% PEG and 25% PEG treatment compared to the control condition. A significant positive correlation exists between the important growth parameters like rate of germination (%), final germination (%), shoot dry weight, root dry weight and vigour index. On the basis of these physiological traits against osmotic stress, nine genotypes of wheat such as BD-480, BD-498, BD- 501, BD-513, BD-514, BD-519, BD-592, BD-618 and BD- 633 were selected as drought tolerant.SAARC J. Agri., 15(2): 177-192 (2017)